2021
DOI: 10.1093/eurheartj/ehab620
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory post-diuretic renal sodium reabsorption is not a dominant mechanism of diuretic resistance in acute heart failure

Abstract: Aims In healthy volunteers, the kidney deploys compensatory post-diuretic sodium reabsorption (CPDSR) following loop diuretic-induced natriuresis, minimizing sodium excretion and producing a neutral sodium balance. CPDSR is extrapolated to non-euvolemic populations as a diuretic resistance mechanism; however, its importance in acute decompensated heart failure (ADHF) is unknown. Methods and results Patients with ADHF in the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…However, some challenges to a global implementation exist as (i) not all cardiology/medicine inpatient wards are equipped with the personnel to perform well timed urine samples, (ii) inconsistencies outside of trial settings occur with regard to the timing of diuretic administration and UNa sampling, sometimes occurring simultaneously (with the sample reflecting a random sample), (iii) incontinence and other patient features such as delirium might interfere with appropriate sample collection, (iv) not all in‐hospital settings have access to 24 h laboratory analysis making UNa analysis after diuretics less actionable as they will be analysed in batch with the day‐shift, and (v) even if laboratory analysis would be available in the middle of the night on a hospitalization ward, physicians to take action on the results might not always be available. Because the peak natriuretic response after a loop diuretic heavily relies on the intrinsic renal sodium avidity, a random UNa sample at the time of ED admission could be an alternative option 18,19 . Identifying a low UNa in a random sample is useful even if patients have received diuretic administration in the hours before, as a low value would still imply poor diuretic response, which is intrinsically linked to the renal sodium avidity state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some challenges to a global implementation exist as (i) not all cardiology/medicine inpatient wards are equipped with the personnel to perform well timed urine samples, (ii) inconsistencies outside of trial settings occur with regard to the timing of diuretic administration and UNa sampling, sometimes occurring simultaneously (with the sample reflecting a random sample), (iii) incontinence and other patient features such as delirium might interfere with appropriate sample collection, (iv) not all in‐hospital settings have access to 24 h laboratory analysis making UNa analysis after diuretics less actionable as they will be analysed in batch with the day‐shift, and (v) even if laboratory analysis would be available in the middle of the night on a hospitalization ward, physicians to take action on the results might not always be available. Because the peak natriuretic response after a loop diuretic heavily relies on the intrinsic renal sodium avidity, a random UNa sample at the time of ED admission could be an alternative option 18,19 . Identifying a low UNa in a random sample is useful even if patients have received diuretic administration in the hours before, as a low value would still imply poor diuretic response, which is intrinsically linked to the renal sodium avidity state.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a simple UNa sample (random sample outside the post‐diuretic phase) has been shown to convey information about the state of intrinsic renal sodium avidity in heart failure and has been shown to be strongly correlated with the post‐diuretic UNa concentration 17–19 . Yet, no studies have investigated the role of assessing the intrinsic renal sodium avidity through a random UNa sample in predicting decongestive response.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been classically described as causes of an impaired diuretic response. Among these, we have: 1) a reduced delivery of diuretic to the kidney's proximal tubule due to reduced cardiac output, which constitutes the cause of the increasingly high diuretic doses required in HF; 2) compensatory sodium reabsorption either after the diuretic effect wears off or at other nephron segments, something that has been described in healthy adults but seems not to occur in patients with AHF (Cox et al, 2021); and 3) congestive nephropathy, where the increased sympathetic tone causes a chronic redistribution of blood into the central circulation, FIGURE 1 | Cardiorenal pathophysiology. Interrelation between heart and kidney in the development of the different types of cardiorenal syndrome (CRS).…”
Section: Congestionmentioning
confidence: 99%
“…CPSR was described in healthy individuals as a decrease in renal sodium secretion after the loop diuretic level drops to concentrations lower than its threshold (Kelly et al, 1983). This phenomenon was not only recently disproven to participate in the development of diuretic resistance in AHF, but that those patients who have a greater diuretic and natriuretic response to furosemide present a larger post-diuretic spontaneous diuresis (Cox et al, 2021).…”
Section: Vasopressin Receptor 2 Antagonistsmentioning
confidence: 99%
“…Multiple studies, old and new, have illustrated that the underlying level of renal sodium avidity is of primary importance in determining diuretic response. (10,29) Some of the seminal work in diuretic response research demonstrated that healthy volunteers provided a very low salt diet had dramatically reduced response to even the first dose of loop diuretic. (10) This prediuretic or basal sodium avidity describes the proclivity of the kidney to excessively retain sodium in the absence of diuretics.…”
Section: Mechanisms Of Loop Diuretic Resistancementioning
confidence: 99%